Advances in Genome Editing and Application to the Generation of Genetically Modified Rat Models - Chenouard, Vanessa; Remy, Séverine; Tesson, Laurent; Ménoret, Séverine; Ouisse, Laure-Hélène; Cherifi, Yacine; Anegon, Ignacio (Frontiers in Genetics, 2021)
The rat has been extensively used as a small animal model. Many genetically engineered rat models have emerged in the last two decades, and the advent of gene-specific nucleases has accelerated their generation in recent years. This review covers the techniques and advances used to generate genetically engineered rat lines and their application to the development of rat models more broadly, such as conditional knockouts and reporter gene strains. In addition, genome-editing techniques that remain to be explored in the rat are discussed. The review also focuses more particularly on two areas in which extensive work has been done: human genetic diseases and immune system analysis. Models are thoroughly described in these two areas and highlight the competitive advantages of rat models over available corresponding mouse versions. The objective of this review is to provide a comprehensive description of the advantages and potential of rat models for addressing specific scientific questions and to characterize the best genome-engineering tools for developing new projects.